PELATIHAN PENINGKATAN KUALITAS GURU DAN PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS DIGITAL DAN NON DIGITAL DI SD NEGERI PANJENG KABUPATEN PONOROGO - Setyansah, Reza Kusuma; Lusiana, Restu; Murtafiah, Wasilatul; Suprapto, Edy; Apriandi, Davi; Krisdiana, Ika (Universitas Mataram, 2024)
The development of the digitalization period is increasingly widespread and requires adaptation of human resources to adapt to today's technology. This is related to the transition period that occurred during the Covid-19 pandemic, during which time all activities were carried out in the learning process boldly and face-to-face learning was not permitted. This really requires adaptation and improvisation for all teachers in Indonesia, especially at Panjeng State Elementary School, Ponorogo district, who are required to be proficient in using electronic devices, especially smartphones and computers. This training is intended to equip all Panjeng State Elementary School teachers in Jenangan District, Ponorogo Regency with skills in creating and managing learning media for students, both digital and non-digital. The aim of this training is to create digital-based learning media and create non-digital learning media, which includes theoretical and practical implementation components. Therefore, the Mathematics Education Study Program at Universitas PGRI Madiun is collaborating with KKN students in 2024 to carry out learning media training activities for Panjeng State Elementary School Teachers in Ponorogo Regency. The activity sessions were divided into two, namely the first training session from the KKN students by creating non-digital based learning media or concrete media and the second training session from the lecturers by creating digital based learning media. The training was carried out smoothly and the success of the activity was seen from the enthusiastic activities of the teachers in observing the media creation process, as well as post-activity evaluation and monitoring where the teachers applied the learning media used in the learning process.